Systematic Review: The Effectiveness of Olive Oil on Oxidative Stress Process in the Development of Atherosclerosis - Musdalifah Alhumaerah; Rachmat Faisal Syamsu; Asrini Safitri (Journal of Community Health Provision, 2026)
This study aims to analyze the antioxidant effects of olive oil, particularly extra virgin olive oil (EVOO), in inhibiting oxidative stress and its role in the development of atherosclerosis. This study employed a systematic review approach by analyzing scientific articles published between 2020 and 2026 from databases such as PubMed, Scopus, Sinta, and Google Scholar. Selected studies examined the effects of olive oil and its bioactive compounds on oxidative stress, inflammation, and cardiovascular risk factors. The findings indicate that EVOO, especially its polyphenol content, plays a significant role in reducing reactive oxygen species (ROS), preventing LDL oxidation, improving endothelial function, and enhancing antioxidant enzyme activity. However, some studies reported inconsistent results depending on dosage, duration, and subject characteristics. Overall, EVOO demonstrates strong potential as a nutritional intervention to prevent and slow the progression of atherosclerosis through antioxidant, anti-inflammatory, and lipid-regulating mechanisms.